2011
DOI: 10.1371/journal.pone.0017230
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Endogenous Toxin, Creatinine from Blood Plasma Depends on Albumin Conformation: Site Specific Uremic Toxicity & Impaired Drug Binding

Abstract: Uremic syndrome results from malfunctioning of various organ systems due to the retention of uremic toxins which, under normal conditions, would be excreted into the urine and/or metabolized by the kidneys. The aim of this study was to elucidate the mechanisms underlying the renal elimination of uremic toxin creatinine that accumulate in chronic renal failure. Quantitative investigation of the plausible correlations was performed by spectroscopy, calorimetry, molecular docking and accessibility of surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Furthermore, our study is the first to confirm the influence of elevated serum urea concentrations on the protein binding of phenytoin in children. Although the biochemical parameters serum urea and serum creatinine are correlated and both influenced protein binding of phenytoin in the univariate analysis, serum urea concentrations can be a better marker for accumulation of uremic toxins than serum creatinine based on the facts that uremic toxins are able to bind to albumin and displace protein-bound drugs 30,31 and that the relationship of serum creatinine with renal function in very young children is different from that in young adults. 32 Even though our study suggests that changes in serum urea concentrations significantly influence the unbound fraction, this effect is rather small and perhaps not clinically relevant in children with a modestly increased serum urea concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study is the first to confirm the influence of elevated serum urea concentrations on the protein binding of phenytoin in children. Although the biochemical parameters serum urea and serum creatinine are correlated and both influenced protein binding of phenytoin in the univariate analysis, serum urea concentrations can be a better marker for accumulation of uremic toxins than serum creatinine based on the facts that uremic toxins are able to bind to albumin and displace protein-bound drugs 30,31 and that the relationship of serum creatinine with renal function in very young children is different from that in young adults. 32 Even though our study suggests that changes in serum urea concentrations significantly influence the unbound fraction, this effect is rather small and perhaps not clinically relevant in children with a modestly increased serum urea concentration.…”
Section: Discussionmentioning
confidence: 99%
“…FTIR spectra of proteins exhibit a number of amide bands, which represent different vibrations of the peptide moiety. Among all the amide bands, the amide I band appears at 1700-1600 cm -1 due to C=O stretch, and amide II band appears at 1600-1500 cm -1 and is associated with C-N stretch and N-H bending mode having relationship with the conformation of proteins [39]. In the two bands, amide I is more sensitive to the changes in protein secondary structure than amide II.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 97%
“…It contains many kinds of coordinating groups, which can combine with many endogenous and exogenous compounds [15][16][17]. Although the toxicity studies of BPF have been reported, the particular interaction mechanism, the mode of BPF with serum albumin and its effect on protein conformation are still unknown.…”
Section: H I G H L I G H T Smentioning
confidence: 99%